Enhancing income and nutritional security in Meghalaya - Babu, Subhash; Das, Anup; Devi, Thoi thoi; Tahashildar, Moutusi; Lyek, Jayantha; Yadav, G S (Indian Horticulture, 2019)
The horticulture based IFS model comprises different modules, viz. crop production (vegetables, fruits and field crops), fishery, poultry, piggery and vermicompost/recycling of farm waste. The system generates year-round income and employment to the farm family. The model generates a net income of 1,66,424 with a monthly saving of `13, 868 as well as 691 mandays of annual employment. Furthermore, the IFS model is about 33% more energy efficient than the practices of the region and have great potential to increase income of small and marginal farmers of Meghalya.